CONSTRUCTING OUT-MIGRATION POTENCY INDEX FROM PROVINCE OF INDONESIA IN 2019 - Efendi, Nadya Namirasepti; Sirait, Timbang (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Out-migration is a solution that people do when their area is unable to fulfill their needs. However, the area of origin that people left behind is even more neglected because many productive and educated people are moving. To know the potency of out-migration, it is necessary to determine the push factors of migration. Lee (1966) and Lewis (1982) state that there are push factors including economic, demographic, environmental, infrastructure, and political factors. This study aims to build a composite indicator that is able to describe the potency of out-migration from a province of Indonesia in 2019. By utilizing data from various BPS’s publications, exploratory factor analysis was carried out with the guide from OECD (2008). As result, four factors were formed, namely economic population and infrastructure factor, welfare and pollution factor, social and security factor, and industrial and clean water factor. DKI Jakarta has the lowest potency and Papua has the highest potency. The correlation between HDI and the Out-Migration Potential Index (OMPI) is -0.798 so that the higher human development in an area, the lower potency to be left by the population. This index is a new index, it can be an illustration that given to the government in dealing regional development’s gap in Indonesia.